Karakteristik dan Kepadatan Sampah Laut pada Ekosistem Padang Lamun di Perairan Sanur, Pulau Bali - Siburian, Eunike; Hendrawan, I Gede; Widiastuti, Widiastuti (Journal of Marine Research and Technology; Vol 8 No 1 (2025): FEBRUARI 2025DO - 10.24843/JMRT.2025.v08.i01.p09, 2025)
Marine debris is one of the global issues that is now receiving serious attention. Economic and tourism growth in Bali Province has led to an increase in waste that is not always matched by an adequate waste management system. This study analyze d the characteristics and density of marine debris in s eagrass e cosystems in Sanur Waters, Bali Island, and the relationship between seagrass density and marine debris density. Garbage collection was conducted at 16 location points covering the entire seagrass ecosystem area in Sanur Waters. The data collection method was performed using the method developed by the Commonwealth Scientific and Industrial Research Organization (CSIRO) Global Plastic Pollution Project, where the marine debris studied was macro. Perpendicular line transects were drawn starting from the discovery of the first seagrass to the open sea along 50 meters with three repetitions at each point, where each repetition was carried out at three different transect locations 50 m apart from each other at each point. Of the various types of waste found, the most dominant kind of waste is plastic, which is 76.98%, dominated by the soft plastic class at as much as 49.01%, hard plastic class at 13.58%, and foam at 12.58%. The size of waste found was dominated by waste, with a size of 8-16 cm, which was as much as 28.15%. As much as 57% of the waste is in the form of whole, and 43% is in the form of fragments. Marine debris was scattered throughout the seagrass ecosystem area of Sanur Water, with debris density ranging from 0.07-0.22 pieces/m 2 with an average value of 0.12 pieces/m 2 . The results of Pearson correlation analysis (r = 0.08) illustrate a less significant relationship between seagrass density and litter density.